Layout of smoke detector for aircraft cargo compartment considering ventilation effect - ZHONG Dechao; YANG Jun; XIE Meng (Hangkong gongcheng jinzhan, 2024)
The cargo compartments of most current aircraft types are equipped with ventilation function. It is of great significance for flight safety to explore the influence of ventilation effect on smoke diffusion in the cargo compartment and determine the layout of smoke detectors in the cargo compartment under ventilation conditions. A numerical model of fire smoke in DC-10 aircraft cargo compartment is established by using computational fluid dynamics method, and the flow field characteristics of fire smoke are analyzed by simulation. POD flow field orthogonal decomposition theory is used to reveal the influence mechanism of ventilation on fire smoke flow field, the layout of smoke detector in smoke cargo compartment under ventilation condition is studied by simulation and experiment. The results show that ventilation can inhibit the upward diffusion of fire smoke and delay the time for smoke to reach the cargo compartment ceiling. With the increase of ventilation volume, the energy proportion of small and medium-sized disordered flow modes in flow field increased, while the energy proportion of large-scale flow modes of smoke moving close to the cargo ceiling decreased, which resulted in a longer time for smoke to reach the ceiling. By comparing the response performance of the three different detector layouts experimentally, it is concluded that the optimal detector layout is to install the detector near the corner of the cargo hold and away from the vent.